Understanding X-ray-induced isomerisation in photoswitchable surfactant assemblies - Jones, Beatrice E.; Blayo, Camille; Greenfield, Jake L.; Fuchter, Matthew J.; Cowieson, Nathan; Evans, Rachel C. (Beilstein Journal of Organic Chemistry, 2024)
Dynamic, responsive materials can be built using photosurfactants (PS) that self-assemble into ordered nanostructures, such as micelles or liquid crystals. These PS contain photoswitchable groups, such as azobenzene (Azo) or, more recently, arylazopyrazoles (AAPs), which change shape and polarity on photoisomerisation between the E and Z states, thus changing the self-assembled structure. Small-angle X-ray scattering (SAXS) is a powerful technique to probe the morphology of PS and can be used to measure the mechanisms of structural changes using in-situ light irradiation with rapid, time-resolved data collection. However, X-ray irradiation has been shown previously to induce Z-to-E isomerisation of Azo-PS, which can lead to inaccuracies in the measured photostationary state. Here, we investigate the effect of light and X-ray irradiation on micelles formed from two different PS, containing either an Azo or AAP photoswitch using SAXS with in-situ light irradiation. The effect of X-ray irradiation on the Z isomer is shown to depend on the photoswitch, solvent, concentration and morphology. We use this to create guidelines for future X-ray experiments using photoswitchable molecules, which can aid more accurate understanding of these materials for application in solar energy storage, catalysis or controlled drug delivery.
Keywords: arylazopyrazole; azobenzene; micelle; photoswitch; X-ray